Body fluid loss during four consecutive Beach Handball matches in high humidity and environmental temperatures - Karras, D.; Chryssanthopoulos, C.; Diafas, V. (Serbian Journal of Sports Sciences, 2007)
The present study investigated the fluid losses that occur in beach handball (BH) when ambient temperature (T) and humidity (H) are high (T > 28 o C; H > 80%). Seven female handball (HB) players who belonged to different first division Greek HB teams took part in an international BH tournament as members of a BH team. In the tournament the players played 4 consecutive matches within two days. During the warm-up, match, and half-time every player ingested one litre of water. Body fluid losses (BFL) were 0.6-0.8 l whereas when BFL were corrected for fluid intake these values were 1.6-1.8 l respectively. When fluid intake was not taken into account, BFL corresponded to about 1% - 1.4% of body mass (BM). When fluid intake was considered, the BFL corresponded to 2.8% - 3.2% of BM. Beach handballers are advised to practice drinking in training so that they will be able to consume fluid during matches that is about 2% of their BM when humidity and temperatures are high. This practice will assist players to avoid excessive hypohydration and maintain body fluid balance.